Die Europäische Agrarpolitik im Spannungsfeld von Osterweiterung und WTO-Verhandlungen: Eine polit-ökonomische Analyse der jüngsten Agrarreform unter besonderer Berücksichtigung von Deutschland und Frankreich - Christian H.C.A. Henning; Thomas Glauben; Andreas Wald (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– EU Enlargement and WTO Restrictions Shaping the CAP - A political economy analysis of the present and future CAP reform with special reference to Germany and France. The paper presents a political economy analysis of the present and future CAP reform induced under different policy scenarios regarding future EU enlargement and future WTO agreements. Theoretically, the analysis is based on a political exchange model suggested by Henning (2000). Main results are: (i) Both present and future CAP reforms are significantly biased by the political influence of farmers' lobby. (ii) In quantitative terms an EU enlargement would induce a much stronger shift in the future CAP when compared to increased WTO restrictions. (iii) The timing of the reform is important, given the fact that induced CAP reforms would be supported by a qualified majority within the EU-15, but within the EU-25 these reforms would be defeated by coalition of the new Eastern European member states using their common veto-power. (iv) The majority of political actors within the EU-15 including both politicians and interest groups evaluate induced CAP reforms negatively in comparison to the status quo, while from society's perspective these imply a positive shift of total economic welfare within EU-15.
Keywords: 330; EU-Agrarpolitik; Internationale Handelspolitik; EU-Mitgliedschaft; EU-Staaten